International environmental agreements: Incentives and political economy - Carlo Carraro; Domenico Siniscalco (Fondazione Eni Enrico Mattei (FEEM), 1997)
International environmental agreements are increasingly important in a globalised economy. Beyond their specific interest, these agreements are also important in the context of coalition formation theory. Given the incentives to free ride, associated to the environment as a public good and to the presence of spillovers, the profitability and the optimality of environmental agreements are separated from their stability (i.e. self-enforcement): hence, a whole set of political economy issues. This paper reviews the recent advances in this area. In particular it discusses mechanisms and strategies aimed at offsetting the incentives to free ride and increasing welfare, such as transfers, issue linkages, threats and multiple agreements. The main results show that partial coalitions and multiple agreements tend to prevail among subsets of players, and that agreements among all players are most unlikely to exist. The design of the agreements, moreover, can be crucial in determining the number of signatory countries.
Keywords: J50; D60; H23; J21; Q43; 330; Coalitions; International Agreements; Environment; Political Economy; Games